Political Integration in the Establishment of Islamic Theological - Miswari; T. Wildan; Amiruddin (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
This article aims to analyze the theological beliefs that have an impact on the formation of political movements and political movements that realize theological schools. This study uses a qualitative approach. The source of the study comes from related references, particularly regarding the development of theology in Islam and its relation to power politics. The findings of the article show that differences in understanding of theology have created the emergence of many groups. Every theological thought has its own argumentation basis. Differences in theological understanding are determined by the understanding of the Qur'an and Hadith. Differences in the meaning of religion are largely determined by reasoning ability and the patron of religious authority that is followed. Each group builds political power to defend and spread its theological understanding. In the early generations, religious patrons had a great opportunity to lead their group's political movements. In the period of its development, the spread of theological schools needed to be integrated with politics. In contrast to the early generations, in later periods, the development of theology depended on the ability of religious authorities to offer an integrative meaning of religion with political power.